Code-Mixing Analysis in an Introductory Lecture by the Indonesian Minister of Finance, Sri Mulyani Indrawati - Violin Yang; Flora Debora Floris (Institute of Research and Community Outreach - Petra Christian University, 2022)
The objective of this study is to investigate the types of code-mixing found in Sri Mulyani Indrawati’s introductory lecture entitled Kuliah Pengantar Ekonomi FEB UI 2019- Sri Mulyani Indrawati, S. E., M.Sc., Ph. D (Introduction to Economics), which was delivered in Universitas Indonesia in 2019. For the analysis, the writers used code-mixing theory proposed by Muysken (2000). The writers implemented qualitative approach to complete this study. The findings of the research showed that all types of code mixing, namely insertion, alternation, and congruent lexicalization, were present. This study also revealed that Indonesian-English pattern dominated the code mixing-cases in this introductory lecture.